Electrochemical devices and electronic devices

By doping specific elements on the positive electrode sheet of the electrochemical device and adding specific salts to the electrolyte solution, a stable solid electrolyte interface film is solved, and the lack of performance of the electrochemical device at low and high temperatures is significantly improved, and voltage stability and safety are significantly improved.

CN119447448BActive Publication Date: 2025-04-04NINGDE AMPEREX TECHNOLOGY LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510049245.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-04
Estimated Expiration
2045-01-13

AI Technical Summary

Technical Problem

Existing electrochemical devices have large voltage drops at low temperatures and high currents, and insufficient puncture performance and intermittent cycle performance at high temperatures, resulting in safety hazards and performance degradation.

Method used

The positive electrode active material layer on the positive electrode sheet is adopted, including two or more of boron, calcium, iron and magnesium, and an appropriate amount of lithium difluorophosphate and lithium difluorosulfonimide are added to the electrolyte to form a better positive electrode solid electrolyte interface film to improve the low-temperature and high-temperature performance of the electrochemical device.

Benefits of technology

Effectively suppress the self-discharge of the battery at low temperatures, improve the puncture performance and intermittent circulation performance at high temperatures, and enhance the overall performance and safety of the electrochemical device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present application discloses an electrochemical device and an electronic device. The electrochemical device of the embodiment of the present application includes a positive electrode plate, an electrolyte, a negative electrode plate and a separator disposed between the positive electrode plate and the negative electrode plate; the positive electrode plate includes a positive electrode active material layer, and the positive electrode active material layer includes two or more of boron, calcium, iron and magnesium elements; the electrolyte includes lithium difluorophosphate, and the mass percentage of the lithium difluorophosphate in the electrolyte is A%, and the value range of A satisfies: 0.02≤A≤0.5; the electrolyte also includes lithium bis(fluorosulfonyl)imide, and the mass percentage of the lithium bis(fluorosulfonyl)imide in the electrolyte is G%, and the value range of A / G satisfies: 0.01≤A / G≤0.1. The electrochemical device of the embodiment of the present application can improve the voltage drop under low temperature and high current, high temperature puncture performance and high temperature intermittent cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of batteries, and in particular to an electrochemical device and an electronic device. Background Art

[0002] Electrochemical devices, especially secondary batteries, are key components for energy storage and supply, and they play an indispensable role in many fields. Currently, electrochemical devices are used in various scenarios, which also brings various problems. Among them, temperature is an important factor affecting the performance of electrochemical devices. Both low and high temperatures can affect the performance of electrochemical devices.

[0003] Therefore, how to solve the impact of temperature on electrochemical devices and improve battery safety has become a difficult problem in the industry. Summary of the invention

[0004] The embodiments of the present application provide an electrochemical device and an electronic device, which can improve the voltage drop under low temperature and high current, high temperature puncture performance and high temperature intermittent cycle performance.

[0005] An electrochemical device provided in an embodiment of the present application includes a positive electrode plate, an electrolyte, a negative electrode plate and a separator arranged between the positive electrode plate and the negative electrode plate; the positive electrode plate includes a positive electrode active material layer, the positive electrode active material layer includes two or more of boron, calcium, iron and magnesium elements; the electrolyte includes lithium difluorophosphate, the mass percentage of lithium difluorophosphate in the electrolyte is A%, and the value range of A satisfies: 0.02≤A≤0.5; the electrolyte also includes lithium bis(fluorosulfonyl)imide, the mass percentage of lithium bis(fluorosulfonyl)imide in the electrolyte is G%, and the value range of A / G satisfies 0.01≤A / G≤0.1.

[0006] In the embodiment of the present application, when the positive electrode active material layer on the positive electrode plate includes two or more of boron, calcium, iron and magnesium elements and the content of lithium difluorophosphate in the electrolyte satisfies 0.02% to 0.5%, the lithium difluorophosphate in the electrolyte can form a good positive electrode solid electrolyte interface film uniformly with the positive electrode active material layer, and the interface film can effectively inhibit the self-discharge of the battery at low temperature, thereby improving the low temperature voltage drop. At the same time, the interface film is also highly stable at high temperature, which can keep the structure of the positive electrode active material stable, reduce the gas generation of the positive electrode plate and the electrolyte reaction, and make the positive electrode plate have a certain strength, thereby improving the puncture performance of the secondary battery at high temperature, and can also improve the intermittent cycle pass rate of the secondary battery at high temperature.

[0007] At the same time, when the ratio of the mass percentage content of lithium difluorophosphate in the electrolyte of the electrochemical device to the mass percentage content of lithium bis(fluorosulfonyl)imide in the electrolyte satisfies: 0.01≤A / G≤0.1, the synergistic effect of the two makes the composition of the solid electrolyte interface film more complex and stable, helps to form a denser and more uniform solid electrolyte interface film, further enhances the interface compatibility between the positive electrode plate and the electrolyte, and improves the cycle performance and rate performance of the electrochemical device.

[0008] In some specific embodiments, the mass percentage of lithium difluorophosphate in the electrolyte is A%, and the value range of A satisfies: 0.02≤A≤0.2.

[0009] In some specific embodiments, the mass percentage of lithium difluorophosphate in the electrolyte is A%, and the value range of A satisfies: 0.05≤A≤0.2.

[0010] In some specific embodiments, the positive electrode active material layer satisfies at least one of the following conditions: (1) the mass percentage content of the boron element in the positive electrode active material layer is B%, and the value range of B satisfies: 0.01≤B≤0.1; (2) the mass percentage content of the calcium element in the positive electrode active material layer is C%, and the value range of C satisfies: 0.01≤C≤0.1; (3) the mass percentage content of the iron element in the positive electrode active material layer is D%, and the value range of D satisfies: 0.001≤D≤0.05; (4) the mass percentage content of the magnesium element in the positive electrode active material layer is E%, and the value range of E satisfies: 0.05≤E≤0.5.

[0011] In this specific embodiment, when the mass percentage of the elements of the positive electrode active material layer on the positive electrode sheet satisfies at least one of the above items, the lithium difluorophosphate in the electrolyte can better form a positive electrode solid electrolyte interface film with the elements on the positive electrode active material layer. The interface film can better suppress the self-discharge of the battery at low temperatures, and the interface film has higher stability at high temperatures.

[0012] In some specific embodiments, the mass percentage of boron in the positive electrode active material layer is B%, the mass percentage of calcium in the positive electrode active material layer is C%, the mass percentage of iron in the positive electrode active material layer is D%, and the mass percentage of magnesium in the positive electrode active material layer is E%, and (B+C+D+E) / A satisfies: 0.2≤(B+C+D+E) / A≤30.

[0013] When the electrochemical device satisfies 0.2≤(B+C+D+E) / A≤30, two or more elements among boron, calcium, iron and magnesium can be evenly distributed in the interface area between the positive electrode solid electrolyte interface film and the positive electrode plate, so as to adjust the charge distribution at the interface, reduce the interface resistance, enhance the bonding force between the positive electrode plate and the positive electrode solid electrolyte interface film, and further improve the low-temperature voltage drop and high-temperature stability of the electrochemical device.

[0014] In some specific embodiments, the electrolyte may further include 1,3-propane sultone, the mass percentage of 1,3-propane sultone in the electrolyte is F%, and the value range of F+GF×G satisfies: 0.5≤F+GF×G≤2.5.

[0015] In this specific embodiment, when the value range of F+GF×G in the electrolyte of the electrochemical device satisfies 0.5≤F+GF×G≤2.5, 1,3-propanesulfonate and lithium bis(fluorosulfonyl)imide act synergistically to further improve the low temperature performance and high temperature performance of the electrochemical device.

[0016] In some specific embodiments, the electrolyte may further include 1,3-propane sultone. The mass percentage of 1,3-propane sultone in the electrolyte is F%, and the value range of F+GF×G satisfies: 1≤F+GF×G≤1.9.

[0017] In some specific embodiments, the isolation membrane includes a base membrane, and the difference between the maximum pore size and the minimum pore size of the base membrane is H; the positive electrode active material layer may also include positive electrode active material particles, and Dv99 and H of the positive electrode active material particles satisfy: 600≤Dv99 / H≤4000.

[0018] In a specific embodiment of the present application, when Dv99 and H of the positive electrode active material particles satisfy: 600≤Dv99 / H≤4000, it can contribute to the formation of the positive electrode solid electrolyte interface film, further improve the uniformity of the positive electrode solid electrolyte interface film, enhance the self-discharge suppression capability of the electrochemical device, and further improve the charge capacity retention rate, high temperature stability and durability of the electrochemical device at low temperatures.

[0019] In some specific embodiments, the isolation membrane includes a coating, and the coating includes one or more of diazine derivatives and triazine derivatives. The diazine derivatives and / or triazine derivatives can effectively reduce the thermal shrinkage of the isolation membrane at high temperatures, and can also optimize the ion channel of the isolation membrane and enhance the affinity between the isolation membrane and the electrolyte.

[0020] In some specific embodiments, the positive electrode plate may further include an additive, the additive including one or more of lithium dihydrogen phosphate and aluminum dihydrogen phosphate; and / or, the positive electrode plate may further include a binder, the binder including at least one functional group of a trihydroxybenzene ring and a cyano group; and / or, the positive electrode plate may further include a conductive agent, the specific surface area of ​​the conductive agent is 650m 2 / g~900m 2 / g.

[0021] In some specific embodiments, the electrolyte satisfies at least one of the following conditions: (1) the electrolyte may further include 2,2-difluoroethyl acetate, the mass percentage of 2,2-difluoroethyl acetate in the electrolyte is 1%, and the value range of I satisfies: 0.01≤I≤13; (2) the electrolyte may further include fluorobenzene, the mass percentage of fluorobenzene in the electrolyte is J%, and the value range of J satisfies: 1.5≤J≤9; (3) the electrolyte may further include 1,2,3-tris(2-cyanato)propane, the mass percentage of 1,2,3-tris(2-cyanato)propane in the electrolyte is K%, and the value range of K satisfies: 0.05≤K≤3; (4) the electrolyte may further include 3-fluoro-4-methylanisole, the mass percentage of 3-fluoro-4-methylanisole in the electrolyte is L%, and the value range of L satisfies: 1≤L≤2.5.

[0022] The electrolyte satisfies any of the above items, which can effectively reduce the high-temperature gas production of the electrochemical device and improve the ESI change rate of the electrochemical device under fast charging.

[0023] In some specific embodiments, the electrolyte satisfies at least one of the following conditions: (1) the value range of I satisfies: 6≤I≤12; (2) the value range of J satisfies: 1.5≤J≤4.5; (3) the value range of K satisfies: 0.05≤K≤2.

[0024] In some specific embodiments, the boron element, calcium element, iron element or magnesium element in the positive electrode active material layer is introduced into the positive electrode active material layer by doping.

[0025] In a second aspect, an electronic device comprises the electrochemical device of the first aspect. DETAILED DESCRIPTION

[0026] The embodiments of the present application will be described in detail below. The embodiments of the present application should not be interpreted as limiting the present application.

[0027] As used in this application, the terms "including," "containing," and "comprising" are used in their open, non-limiting sense.

[0028] In addition, sometimes amounts, ratios and other numerical values ​​are presented in range format herein. It should be understood that such range format is for convenience and brevity, and should be flexibly understood to include not only the numerical values ​​explicitly specified as range limits, but also all individual numerical values ​​or sub-ranges encompassed within the range, as if each numerical value and sub-range were explicitly specified.

[0029] In the detailed description and claims, a list of items connected by the terms "one or more of," "one or more of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A or B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, or C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.

[0030] In today's technology-driven era, electrochemical devices, especially secondary batteries, as key components for energy storage and supply, play an indispensable role in many fields. From the power source of electric vehicles to the energy guarantee of various portable electronic devices, to the construction of large-scale energy storage systems, its application scenarios are becoming increasingly extensive and in-depth.

[0031] However, low temperature and high current working conditions pose severe challenges to electrochemical devices. When the ambient temperature decreases, the physical and chemical properties of the electrolyte change significantly, its viscosity increases significantly, and the ion conduction rate drops sharply. For example, the degree of dissociation of lithium salts in common lithium-ion battery electrolytes decreases, and the movement of solvent molecules becomes sluggish, which seriously hinders the migration of lithium ions between electrodes and electrolytes under high current demands. The ohmic resistance increases, and the electrochemical polarization intensifies, resulting in a significant voltage drop in the battery output voltage. This phenomenon is particularly prominent when electric vehicles are driving in winter. It not only severely limits the vehicle's cruising range, but may also cause misjudgment of the battery management system or other safety hazards due to low voltage, such as over-discharge or unbalanced charging and discharging of battery cells, which in turn has a negative impact on the overall life of the battery.

[0032] Electrochemical devices face many risks in high-temperature environments. High-temperature puncture performance has become one of the key issues. During the production, transportation, installation and actual use of the battery, it is possible to encounter unexpected mechanical punctures. Because high temperature significantly increases the activity of the chemical reaction inside the battery, once a puncture occurs, the short circuit between the positive and negative electrodes will instantly trigger a violent thermal runaway reaction. A strong redox reaction will occur between the electrode material and the electrolyte, generating a large amount of heat, causing the electrolyte to boil and vaporize, and the internal pressure of the battery to rise sharply. If it cannot be effectively controlled, it will cause catastrophic consequences such as battery fire and explosion, posing a huge threat to human life and property.

[0033] In addition, high-temperature intermittent cycle conditions are also very common in practical applications, such as frequent start-stop and charge of electric vehicles in hot weather, and charge and discharge cycle operations of energy storage power stations in hot seasons. In this case, the high temperature environment inside the battery accelerates the rate of side reactions between the electrode material and the electrolyte. For example, the positive electrode material may undergo structural phase changes and transition metal dissolution, resulting in a gradual increase in the internal resistance of the battery and a continuous decrease in capacity. Moreover, repeated high-temperature intermittent cycles will change the stress distribution inside the battery, further affecting the integrity of the electrode structure, reducing the cycle life and reliability of the battery, increasing the cost of use and limiting its long-term stable application in high-temperature environments.

[0034] In view of the above problems, the present application provides an electrochemical device and an electronic device, which can improve the voltage drop under low temperature and high current, high temperature puncture performance and high temperature intermittent cycle performance. The implementation methods of the present application are described in detail below.

[0035] Electrochemical Devices

[0036] In a first aspect, the present application provides an electrochemical device, comprising a positive electrode plate, an electrolyte, a negative electrode plate and an isolation membrane arranged between the positive electrode plate and the negative electrode plate; wherein the positive electrode plate comprises a positive electrode active material layer, the positive electrode active material layer comprises two or more of boron, calcium, iron and magnesium elements; the electrolyte comprises lithium difluorophosphate, the mass percentage of lithium difluorophosphate in the electrolyte is A%, and the value range of A satisfies: 0.02≤A≤0.5; the electrolyte also comprises lithium bis(fluorosulfonyl)imide, the mass percentage of lithium bis(fluorosulfonyl)imide in the electrolyte is G%, and the value range of A / G satisfies: 0.01≤A / G≤0.1.

[0037] For example, the positive electrode active material layer of the positive electrode plate of the electrochemical device of the present application may include boron and calcium, boron and iron, boron and magnesium, calcium and iron, calcium and magnesium, iron and magnesium, boron, calcium and iron, boron, calcium and magnesium, calcium, iron and magnesium, or boron, calcium, iron and magnesium.

[0038] For example, the boron element in the positive electrode active material can be introduced by doping or coating with a boron source, and the boron source can come from one or more of boron oxide, boric acid, boron fluoride, boron powder, boron nitride and cobalt boride; the calcium element in the positive electrode active material can be introduced by doping or coating with a calcium source, and the calcium source can come from one or more of calcium carbonate, calcium oxide, calcium nitrate, calcium hydroxide, perovskite substances, calcium fluorophosphate and calcium phosphate; the iron element in the positive electrode active material can be introduced by doping or coating with an iron source, and the iron source can come from one or more of iron oxide, iron sulfide, inorganic iron salt, ferrocyanide and iron-containing metal organic framework materials (MOFs); the magnesium element in the positive electrode active material can be introduced by doping or coating with a magnesium source, and the magnesium source can be one or more of magnesium-based oxides, magnesium hydroxide, inorganic magnesium salts and magnesium metal organic framework materials (MOFs).

[0039] A can be 0.02, 0.04, 0.08, 0.08, 0.1, 0.12, 0.14, 0.16, 0.18, 0.2, 0.22, 0.24, 0.26, 0.28, 0.3, or a range consisting of any of the above values.

[0040] A / G may be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, or a range consisting of any of the above values.

[0041] Optionally, 0.02≤A≤0.2, 0.022≤A≤0.2, 0.025≤A≤0.2, 0.028≤A≤0.2, 0.03≤A≤0.2, 0.032≤A≤0.2, 0.035≤A≤0.2, 0.038≤A≤0.2, 0.04≤A≤0.2, 0.042≤A≤0.2, 0.045≤A≤0.2, 0.048≤A≤0.2, and 0.05≤A≤0.2.

[0042] According to the present application, when the positive electrode active material layer on the positive electrode plate of the electrochemical device includes two or more of boron, calcium, iron and magnesium elements and the content of lithium difluorophosphate in the electrolyte satisfies 0.02%~0.5%, the lithium difluorophosphate in the electrolyte can uniformly form a good positive electrode solid electrolyte interface film with the positive electrode active material layer, and the interface film can effectively inhibit the self-discharge of the battery at low temperature, thereby improving the low temperature voltage drop. At the same time, the interface film is also highly stable at high temperature, which can keep the structure of the positive electrode active material stable, reduce the gas production of the reaction between the positive electrode plate and the electrolyte, and make the positive electrode plate have a certain strength, thereby improving the puncture performance of the secondary battery at high temperature, and can also improve the intermittent cycle pass rate of the secondary battery at high temperature.

[0043] At the same time, when the ratio of the mass percentage content of lithium difluorophosphate to the mass percentage content of lithium bis(fluorosulfonyl)imide in the electrolyte satisfies: 0.01≤A / G≤0.1, the synergistic effect of the two makes the composition of the solid electrolyte interface film more complex and stable, helps to form a denser and more uniform solid electrolyte interface film, further enhances the interface compatibility between the positive electrode plate and the electrolyte, and improves the cycle performance and rate performance of the electrochemical device.

[0044] It should be noted that the element type of the positive electrode active material layer, the mass percentage of lithium difluorophosphate in the electrolyte is A%, and the mass percentage of lithium bis(fluorosulfonyl)imide is G% can all be detected using methods and instruments known in the art. For example, the electrochemical device can be disassembled, centrifuged to obtain the electrolyte, and tested by ion chromatography (IC), and some components in the electrolyte (such as lithium salt) are qualitatively identified by retention time, and the corresponding mass percentage is calculated by peak area; the mass percentage of some components in the electrolyte (such as organic solvent) is detected by gas chromatography-mass spectrometry (GC-MS), thereby obtaining A; the element type can be determined by measuring the binding energy of the inner-shell electrons of the elements in the positive electrode active material layer by X-ray photoelectron spectrometry (XPS). When the positive electrode active material layer is irradiated with X-rays, the inner-shell electrons of the atoms are excited to escape and generate photoelectrons. The photoelectrons of different elements have different binding energies. By analyzing the energy distribution of the photoelectrons, the element types and their chemical states present in the positive electrode active material layer can be determined.

[0045] In some embodiments, the positive electrode active material layer of the positive electrode sheet of the electrochemical device of the present application satisfies at least one of the following conditions: (1) the mass percentage content of the boron element in the positive electrode active material layer is B%, and the value range of B satisfies: 0.01≤B≤0.1, for example, B can be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, or a range composed of any of the above values; (2) the mass percentage content of the calcium element in the positive electrode active material layer is C%, and the value range of C satisfies: 0.01≤C≤0.1, for example, C can be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, or any range consisting of the above values; (3) the mass percentage content of iron in the positive electrode active material layer is D%, and the value range of D satisfies: 0.001≤D≤0.05, for example, D can be 0.001, 0.005, 0.01, 0.015, 0.02, 0.025, 0.03, 0.035, 0.04, 0.045, 0.05, or any range consisting of the above values; (4) the mass percentage content of magnesium in the positive electrode active material layer is E%, and the value range of E satisfies: 0.05≤E≤0.5, for example, E can be 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, or any range consisting of the above values.

[0046] According to this embodiment, when the mass percentage of the elements of the positive electrode active material layer on the positive electrode plate of the electrochemical device satisfies at least one of the above items, the lithium difluorophosphate in the electrolyte can better form a positive electrode solid electrolyte interface film with the elements on the positive electrode active material layer. The interface film can better suppress the self-discharge of the battery at low temperatures, and at the same time, the interface film has higher stability at high temperatures.

[0047] It should be noted that the element content of the positive electrode active material layer can be detected using methods and instruments known in the art. For example, an inductively coupled plasma mass spectrometer (ICP-MS) can be used to first ionize the elements in the sample by ICP, and then the ions are mass analyzed and detected by a mass spectrometer.

[0048] In some embodiments, the mass percentage of boron element in the positive electrode active material layer of the electrochemical device of this embodiment is B%, the mass percentage of calcium element in the positive electrode active material layer is C%, the mass percentage of iron element in the positive electrode active material layer is D%, and the mass percentage of magnesium element in the positive electrode active material layer is E%, and (B+C+D+E) / A satisfies: 0.2≤(B+C+D+E) / A≤30, for example, it can be 0.2, 0.5, 1, 2, 4, 6, 8, 10, 12, 14, 16, 18, 20, 22, 24, 26, 28, 30, or a range consisting of any of the above numerical values.

[0049] In the above embodiment, when the electrochemical device satisfies 0.2≤(B+C+D+E) / A≤30, two or more of the boron element, calcium element, iron element and magnesium element can be evenly distributed in the interface area between the positive electrode solid electrolyte interface film and the positive electrode plate, so as to adjust the charge distribution at the interface, reduce the interface resistance, enhance the bonding force between the positive electrode plate and the positive electrode solid electrolyte interface film, and further improve the low-temperature voltage drop and high-temperature stability of the electrochemical device.

[0050] In some embodiments, the electrolyte of the electrochemical device of this embodiment may further include 1,3-propanesulfonate, and the mass percentage of 1,3-propanesulfonate in the electrolyte is F%, and the value range of F+GF×G satisfies: 0.5≤F+GF×G≤2.5, for example, F+GF×G can be 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, 2.1, 2.2, 2.3, 2.4, 2.5, or a range consisting of any of the above values.

[0051] Optionally, 0.6≤F+GF×G≤2.5, 0.7≤F+GF×G≤2.5, 0.8≤F+GF×G≤2.5, 0.9≤F+GF×G≤2.5, 1≤F+GF×G≤2.5, 0.5≤F+GF×G≤2.4, 0.5≤F+GF×G≤2.3, 0.5≤F+GF×G≤2.2, 0.5≤F+GF×G≤2.1, 0.5≤F+GF×G≤2, 0.5≤F+GF×G≤1.9.

[0052] According to this embodiment, when F+GF×G in the electrolyte of the electrochemical device satisfies the above range, 1,3-propanesultone and lithium bis(fluorosulfonyl)imide act synergistically to further improve the low temperature performance and high temperature performance of the electrochemical device.

[0053] In some embodiments, the isolation membrane of the electrochemical device of the present embodiment includes a base membrane, and the difference between the maximum pore size and the minimum pore size of the base membrane is H; the positive electrode active material layer may also include positive electrode active material particles, and the Dv99 and H of the positive electrode active material particles satisfy: 600≤Dv99 / H≤4000, for example, Dv99 / H can be 600, 800, 1000, 1200, 1400, 1600, 1800, 2000, 2200, 2400, 2600, 2800, 3000, 3200, 3400, 3600, 3800, 4000, or a range consisting of any of the above numerical values.

[0054] According to this embodiment, when Dv99 and H of the positive electrode active material particles satisfy: 600≤Dv99 / H≤4000, it can contribute to the formation of the positive electrode solid electrolyte interface film, further improve the uniformity of the positive electrode solid electrolyte interface film, enhance the self-discharge suppression ability of the electrochemical device, and further improve the charge capacity retention rate, high temperature stability and durability of the electrochemical device at low temperature.

[0055] It should be noted that the Dv99 of the positive electrode active material particles has a well-known meaning in the art, which indicates the particle size corresponding to the cumulative volume fraction of 99% in the volume-based particle size distribution of the positive electrode active material particles, and can be measured by methods and instruments known in the art. For example, it can be measured by a laser particle size analyzer (such as the British Malvern Mastersizer 2000E) with reference to GB / T 19077-2016 particle size distribution laser diffraction method. The pore size of the diaphragm can be measured by known methods and instruments, such as using an pore size tester to obtain the pore size distribution curve of the diaphragm to obtain the maximum pore size and minimum pore size of the diaphragm.

[0056] In some embodiments, the isolation membrane of the electrochemical device of this embodiment includes a coating, and the coating includes one or more of diazine derivatives and triazine derivatives. The diazine derivatives and / or triazine derivatives can effectively reduce the thermal shrinkage of the isolation membrane at high temperatures, and can optimize the ion channel of the isolation membrane and enhance the affinity between the isolation membrane and the electrolyte.

[0057] In some embodiments, the positive electrode plate may further include an additive, the additive including one or more of lithium dihydrogen phosphate and aluminum dihydrogen phosphate. The use of the above additives can effectively improve the structural strength and chemical stability of the positive electrode plate, thereby improving the thermal stability of the electrochemical device; and / or, the positive electrode plate may further include a binder, the binder including at least one functional group of a trihydroxybenzene ring and a cyano group, for example, the binder may be polyvinylidene fluoride (PVDF), cyano-modified polyvinylidene fluoride (PVDF-CN), cyano-modified polypropylene derivatives, trihydroxybenzene ring-modified polyacrylonitrile derivatives, polyaniline derivatives, acrylonitrile copolymers, hydrogenated nitrile rubber and core-shell type cyanide-containing copolymer acrylic acid aqueous adhesives, etc. The use of the above binder can effectively enhance the mechanical strength of the positive electrode plate, thereby improving the mechanical properties of the electrochemical device; and / or, the positive electrode plate may further include a conductive agent, the specific surface area of ​​the conductive agent is 650m 2 / g~900m 2 / g, for example, the conductive agent can be one or more of conductive carbon black, acetylene black, Ketjen black, graphene, carbon nanotubes and carbon fibers. The use of conductive agents with the above specific surface areas can construct an efficient conductive network, optimize electrode reaction kinetics, improve the structural stability of the positive electrode sheet, and reduce the interface resistance between the electrolyte and the active material, thereby improving the electrical performance of the electrochemical device.

[0058] In some embodiments, the electrolyte of the electrochemical device of this embodiment satisfies at least one of the following conditions: (1) the electrolyte may further include 2,2-difluoroethyl acetate, and the mass percentage content of 2,2-difluoroethyl acetate in the electrolyte is I%, and the value range of I satisfies: 0.01≤I≤13, for example, I can be 0.01, 0.05, 0.1, 0.2, 0.5, 0.8, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, or a range consisting of any of the above values; (2) the electrolyte may further include fluorobenzene, and the mass percentage content of fluorobenzene in the electrolyte is J%, and the value range of J satisfies: 1.5≤J≤9, for example For example, J may be 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, or any range thereof; (3) the electrolyte may further include 1,2,3-tris(2-cyano)propane, and the mass percentage of 1,2,3-tris(2-cyano)propane in the electrolyte is K%, and the value range of K satisfies: 0.05≤K≤3, for example, K may be 0.05, 0.1, 0.2, 0.4, 0.6, 0.8, 1, 1.2, 1.4, 1.6, 1.8, 2, 2.2, 2.4, 2.6, 2.8, 3, or any range thereof. The electrolyte may further include 3-fluoro-4-methylanisole, wherein the mass percentage of 3-fluoro-4-methylanisole in the electrolyte is L%, and the electrolyte satisfies: 1≤L≤2.5, for example, L may be 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, 2.1, 2.2, 2.3, 2.4, 2.5, or a range consisting of any of the above values,

[0059] Optional, 0.1≤I≤13, 0.5≤I≤13, 1≤I≤13, 2≤I≤13, 3≤I≤13, 4≤I≤13, 5≤I≤13, 6≤I≤13, 6≤I≤12.

[0060] Optionally, 1.5≤J≤8.5, 1.5≤J≤8, 1.5≤J≤7.5, 1.5≤J≤7, 1.5≤J≤6.5, 1.5≤J≤6, 1.5≤J≤5.5, 1.5≤J≤5, and 1.5≤J≤4.5.

[0061] Optionally, 0.05≤K≤2.9, 0.05≤K≤2.8, 0.05≤K≤2.7, 0.05≤K≤2.6, 0.05≤K≤2.5, 0.05≤K≤2.4, 0.05≤K≤2.3, 0.05≤K≤2.2, 0.05≤K≤2.1, and 0.05≤K≤2.

[0062] In the above embodiments, the electrolyte satisfies any of the above items, which can effectively reduce the high-temperature gas production of the electrochemical device and improve the ESI change rate of the electrochemical device under fast charging.

[0063] In some embodiments, the boron element, calcium element, iron element or magnesium element in the positive electrode active material layer is introduced into the positive electrode active material layer by doping.

[0064] The following embodiments may enable those skilled in the art to more fully understand the present application, but do not limit the present application in any way.

[0065] In some embodiments, the electrolyte may include additives such as diethylene sulfate (DTD), vinylene sulfate (VC), 1,3-propane sultone and may further include fluoromethyl methyl carbonate, difluoromethyl methyl carbonate, trifluoromethyl methyl carbonate, trifluoroethyl methyl carbonate or bis(trifluoroethyl) carbonate.

[0066] In some embodiments, in addition to LiFSI and LiPO2F2, the electrolyte may further include an ionizable lithium salt, and the ionizable lithium salt includes at least one of LiPF6, LiSbF6, LiAsF6, LiClO4, LiN(C2F5SO2)2, CF3SO3Li, LiC(CF3SO2)3 or LiC4BO8. The concentration of the ionizable lithium salt in the electrolyte is not particularly limited, preferably 0.5 mol / L or more, more preferably 0.8 mol / L or more, and further preferably 1.0 mol / L or more. In addition, it is preferably 3 mol / L or less, more preferably 2 mol / L or less, and further preferably 1.7 mol / L or less. If the concentration of these ionizable lithium salts is too low, it may cause the number of mobile lithium ions in the electrolyte to be insufficient. On the other hand, if the concentration of these ionizable lithium salts is too high, it may cause the viscosity of the electrolyte to increase, resulting in an increase in the impedance of the electrolyte, which reduces the migration rate of lithium ions, and thus may cause the performance of the electrochemical device to decrease.

[0067] In some embodiments, the electrolyte may further include at least one of fluoroether, fluoroethylene carbonate or ether solvents. In some embodiments, the electrolyte may further include a non-aqueous solvent. The non-aqueous solvent may be a carbonate compound, a carboxylate compound, an ether compound, other organic solvents or a combination thereof.

[0068] The carbonate compound may include not only a chain carbonate compound, but also a cyclic carbonate compound, a fluorinated carbonate compound or a combination thereof.

[0069] In addition to diethyl carbonate (DEC) defined in the present application, examples of chain carbonate compounds may include ethyl propionate (EP), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC) and combinations thereof. Examples of cyclic carbonate compounds are ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinyl ethylene carbonate (VEC) or combinations thereof. Examples of the fluorinated carbonate compound are fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, trifluoromethylethylene carbonate, or a combination thereof.

[0070] Examples of the carboxylic acid ester compound are methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanolide, valerolactone, mevalonolactone, caprolactone, methyl formate, or a combination thereof.

[0071] Examples of the ether compound are dibutyl ether, tetraglyme, diglyme, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran, or a combination thereof.

[0072] Examples of other organic solvents are dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate, and phosphoric acid esters or combinations thereof.

[0073] The present application also provides an electrochemical device, comprising the above-mentioned electrolyte. In some embodiments, the electrochemical device further comprises a positive electrode sheet, a negative electrode sheet and a separator, wherein the positive electrode sheet and the negative electrode sheet are separated by a separator disposed therebetween. In some embodiments, the positive electrode sheet comprises a positive current collector and a positive electrode active material layer disposed on the positive current collector, the positive electrode active material layer may include a positive electrode active material and an additive, and the negative electrode sheet comprises a negative current collector and a negative electrode active material layer disposed on the negative current collector, the negative electrode active material layer may include a negative electrode active material.

[0074] In some embodiments, the negative electrode plate may include a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector. The negative electrode active material layer may be disposed on one or both sides of the negative electrode current collector. In some embodiments, the negative electrode current collector may be at least one of a copper foil, a nickel foil, or a carbon-based current collector. In some embodiments, the thickness of the negative electrode current collector may be 1 μm to 200 μm. In some embodiments, the negative electrode active material layer may be coated only on a partial area of ​​the negative electrode current collector. In some embodiments, the thickness of the negative electrode active material layer may be 10 μm to 500 μm. It should be understood that these are exemplary only and other suitable thicknesses may be used.

[0075] In some embodiments, as described above, the negative electrode active material layer includes a negative electrode active material. In some embodiments, the negative electrode active material includes at least one of natural graphite, artificial graphite, or a silicon-based material. In some embodiments, the silicon-based material includes at least one of silicon, a silicon-oxygen compound, a silicon-carbon compound, or a silicon alloy.

[0076] In some embodiments, the negative electrode active material layer may also include a negative electrode conductor and / or a negative electrode binder. The negative electrode conductor may include at least one of carbon black, acetylene black, Ketjen black, graphene, carbon nanotubes, or carbon fibers. In some embodiments, the negative electrode binder may include at least one of carboxymethyl cellulose (CMC), polyacrylic acid, polyacrylic acid salt, polyacrylate, polyvinyl pyrrolidone, polyimide, polysiloxane, or styrene-butadiene rubber. It should be understood that the materials disclosed above are only exemplary, and the negative electrode active material layer may be any other suitable material. In some embodiments, the mass ratio of the negative electrode active material, the negative electrode conductor, and the negative electrode binder in the negative electrode active material layer may be (80~99): (0.5~10): (0.5~10), and it should be understood that this is only exemplary and not intended to limit the present application.

[0077] In some embodiments, the positive electrode plate includes a positive current collector and a positive active material layer disposed on the positive current collector. The positive active material layer may be located on one side or both sides of the positive current collector. In some embodiments, the positive current collector may be made of aluminum foil, and of course, other positive current collectors commonly used in the art may also be used. In some embodiments, the thickness of the positive current collector may be 1 μm to 200 μm. In some embodiments, the positive active material layer may be coated only on a partial area of ​​the positive current collector. In some embodiments, the thickness of the positive active material layer may be 20 μm to 490 μm, and further preferably, the thickness may be 20 μm to 400 μm, and further, it may be 40 μm to 120 μm, and further, it may be 40 μm to 90 μm.

[0078] In some embodiments, as described above, the positive electrode active material layer includes a positive electrode active material. In some embodiments, the positive electrode active material may include at least one of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, or lithium nickel manganese oxide, and the above positive electrode active material may be doped and / or coated. Further preferably, the positive electrode active material is lithium cobalt oxide or lithium iron phosphate.

[0079] In some embodiments, the surface of the positive electrode material includes lithium phosphate and / or lithium niobate, the mass ratio of the two is 1:3 to 1:1, and the thickness of the covering layer is 1 μm to 1.8 μm.

[0080] In some embodiments, the surface of the positive electrode material includes lithium dihydrogen phosphate or aluminum dihydrogen phosphate, and the mass percentage of lithium dihydrogen phosphate or aluminum dihydrogen phosphate is M% based on the total mass of the positive electrode active material layer, and 5≤M≤20.

[0081] In some embodiments, the substrate of the isolation film includes at least one of polyethylene, polypropylene, polyvinylidene fluoride, polyethylene terephthalate, polyimide or aramid. For example, polyethylene includes at least one selected from high-density polyethylene, low-density polyethylene or ultra-high molecular weight polyethylene. In particular, polyethylene and polypropylene have a good effect on preventing short circuits and can improve the safety of the battery through the shutdown effect. In some embodiments, the thickness of the isolation film as a whole is in the range of about 3 μm to 480 μm.

[0082] In some embodiments, the surface of the isolation membrane may further include a porous layer, which is disposed on at least one surface of the isolation membrane, and the porous layer includes inorganic particles and a binder, and the inorganic particles are selected from at least one of aluminum oxide (Al2O3), silicon oxide (SiO2), magnesium oxide (MgO), titanium oxide (TiO2), hafnium dioxide (HfO2), tin oxide (SnO2), cerium dioxide (CeO2), nickel oxide (NiO), zinc oxide (ZnO), calcium oxide (CaO), zirconium oxide (ZrO2), yttrium oxide (Y2O3), silicon carbide (SiC), boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, or barium sulfate. In some embodiments, the pores of the isolation membrane have a diameter in the range of about 0.01 μm to 1 μm. The binder of the porous layer is selected from at least one of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, sodium carboxymethyl cellulose, polyvinylpyrrolidone, polyvinyl ether, polytetrafluoroethylene, or polyhexafluoropropylene. The porous layer on the surface of the separator can improve the heat resistance, oxidation resistance and electrolyte wetting performance of the separator, and enhance the adhesion between the separator and the pole piece. One surface of the separator can also include a high melting point crystalline polymer or a high temperature resistant amorphous polymer, and the high temperature resistant resin includes at least one of polypropylene, poly-4-methylpentene, polytetrafluoroethylene, polyvinylidene fluoride and cycloolefin copolymers. The high melting point crystalline polymer includes at least one of polypropylene, poly-4-methylpentene, polytetrafluoroethylene or polyvinylidene fluoride, and the high temperature resistant amorphous polymer includes cycloolefin copolymers. Based on the mass of the polyolefin porous substrate, the mass percentage z of the high temperature resistant resin is 2.5% to 9%. For example, the mass percentage z of the high temperature resistant resin is 2.5%, 3%, 5%, 7%, 8%, 9% or a range composed of any two of the values. When the above-mentioned types of high temperature resistant resins are added to the polyolefin porous substrate and the mass percentage of the high temperature resistant resin is regulated within the above range, it is beneficial to increase the melting temperature of the separator, improve the strength and high temperature performance of the electrochemical device.

[0083] In some embodiments, the electrochemical device is a lithium-ion battery, but the present application is not limited thereto.

[0084] In some embodiments of the present application, taking lithium-ion batteries as an example, the positive electrode sheet, the isolation membrane, and the negative electrode sheet are wound or stacked in sequence to form an electrode assembly, and then placed in a shell such as an aluminum-plastic film for packaging, and the electrolyte is injected, formed, and packaged to make a lithium-ion battery.

[0085] Embodiments of the present application also provide electronic devices including the above-mentioned electrochemical devices. The electronic devices of the embodiments of the present application are not particularly limited, and they can be any electronic devices known in the prior art. In some embodiments, the electronic device can include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an e-book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.

[0086] Test Section

[0087] (1) Voltage drop test of lithium-ion battery at low temperature:

[0088] At -10°C, the lithium-ion battery is charged to 4.3V at 1C constant current, then charged to 0.05C at constant voltage, and then discharged to 2.0V at 1C constant current, left to stand for 5 minutes, and then the voltage is tested as the pre-storage voltage. After storing at -20°C for 24 hours, the voltage is re-tested as the post-storage voltage. The voltage drop of the lithium-ion battery is calculated according to the following formula: voltage drop = pre-storage voltage - post-storage voltage.

[0089] (2) 80℃ puncture pass rate test:

[0090] At room temperature, charge the lithium-ion battery at a constant current of 0.5C to a voltage of 4.3V, and then charge at a constant voltage to a current of 0.025C; transfer the lithium-ion battery to the nail penetration test equipment, maintain the test environment temperature at 25°C, use a steel nail with a diameter of 4mm to uniformly penetrate the negative electrode ear side at a distance of 7mm from the side of the battery cell at a speed of 30mm / s, and retain it for 300s. The lithium-ion battery is considered to have passed if it does not catch fire or explode.

[0091] Ten batteries were tested for each embodiment / comparative example, and the pass rate of the puncture test = the number of batteries that passed the puncture / the total number of batteries punctured.

[0092] (3) Capacity retention test after 300 intermittent cycles at 60°C:

[0093] At 60°C, the lithium-ion battery was allowed to stand for 30 minutes; it was charged to 4.5V at a constant current rate of 0.5C, and charged to 0.05C at a constant voltage rate of 4.5V; the battery was allowed to stand in a 60°C environment for 24 hours; the battery was cross-current discharged to 3.0V at a rate of 0.5C, and the battery discharge capacity was recorded; this was a complete intermittent charge and discharge cycle, and the battery was charged and discharged 300 times in the same way.

[0094] The capacity retention rate (%) of the lithium-ion battery after the 300th cycle = the discharge capacity at the 300th cycle / the first discharge capacity × 100%.

[0095] (4) Gas production test after storage at 60℃ for 72h:

[0096] At 60°C, the battery was cycled for 3 cycles at a rate of 0.5C and then stored for 72 hours. The test voltage was 2.0V-4.5V, and the battery gas production test device was used to detect the gas production after the battery cycle.

[0097] (5) EIS change rate test under fast charging:

[0098] The AC impedance value was tested by an electrochemical workstation, and the initial impedance was measured to be E1 (Ω). It was charged to 4.2V at a current density of 0.5C and discharged to 3V at 0.5C. After 200 cycles, the AC impedance of the 200th cycle was measured to be E2 (Ω), and the EIS change rate was: [(E2-E1) / E1]×100%.

[0099] (6) 140℃ hot box test pass rate test:

[0100] Step 1: Charge the prepared battery at a constant current of 0.5C to a cut-off voltage of 4.2V, then charge at a constant voltage to a cut-off current of 200mA, and then let it stand for 5 minutes;

[0101] Step 2: Attach the temperature-sensing wire to the fully charged battery between the two tabs, connect the two tabs to monitor the voltage, and hang the battery cell vertically in the box;

[0102] Step 3: Heat the heat box to 145°C at a rate of 5°C and maintain for 60 minutes.

[0103] Judging criteria: The battery passes if it does not catch fire or explode. Count the number of batteries that pass the hot box test.

[0104] (7) Drop test pass rate:

[0105] Under the environmental condition of 25℃, record the open circuit voltage and internal resistance of the battery (the test instrument is a voltage resistance tester, manufacturer: Dongguan Lijia Precision Instrument Co., Ltd., model: LNG-SY1-0020-DQ); 2) Put the battery into the fixture bin, and use the automatic drop device to drop the fixture bin with the battery from the 1m position to the cement bottom plate in the way of landing on the bottom surface of the fixture bin head, the left side, the right side, the back side, the front side, and the top side in a round. One cycle is a total of 3 rounds, that is, 18 times; 3) Then drop the fixture bin with the bottom surface of the fixture bin head. The battery is dropped from a position of 1.5m to a cement floor in the following order: front, left, right, back, front, and top. A total of 3 drops, or 18 times, are performed in one cycle; 4) The battery voltage is measured after each drop. If the battery catches fire or leaks, the drop is stopped. Otherwise, the drop is continued; 5) The battery voltage and internal resistance are recorded. If the voltage drop is <10mV within 24h and the battery packaging bag is not opened or broken, and the battery does not catch fire, leak, or explode, the battery is judged to have passed the drop test. Otherwise, it is considered to have failed. Drop test pass rate = (number of products that passed the drop test ÷ total number of products that participated in the drop test) × 100%.

[0106] (8) 3C charging capacity retention rate at -15℃:

[0107] At -15°C, the lithium-ion battery was left standing for 30 minutes; it was charged to 4.2V at a constant current rate of 0.5C, and charged to 0.05C at a constant voltage rate of 4.2V; the battery was left standing in a -15°C environment for 24 hours; the battery was cross-current discharged to 3.0V at a rate of 0.5C, and the battery discharge capacity was recorded; this was a complete charge and discharge cycle process, and the battery was charged and discharged 300 times in the same way.

[0108] Capacity retention rate (%) of the lithium ion battery after the 300th cycle = discharge capacity at the 300th cycle / initial discharge capacity×100%.

[0109] (9) Electrolyte component test:

[0110] The electrolyte components were tested by GC-MS and combined with the external standard method.

[0111] The measurement of other parameters can be tested by methods commonly known in the art, and this application does not limit them.

[0112] Example

[0113] The following examples describe the disclosure of the present application in more detail, and these examples are intended for illustrative purposes only, as various modifications and variations within the scope of the disclosure of the present application are apparent to those skilled in the art. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by weight, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.

[0114] Example 1-1

[0115] Positive electrode: The positive electrode active material particles, lithium cobalt oxide LiCoO2 (Dv99 is 30μm), are solid-phase doped with boron source and calcium source to obtain doped positive electrode active material particles. The doped positive electrode active material particles and conductive agent Super-P (specific surface area is 800m 2 / g), additive aluminum dihydrogen phosphate, binder cyano modified polyvinylidene fluoride (PVDF-CN) are mixed in a mass ratio of 97:1:2:X, N-methylpyrrolidone (NMP) is added, and an acrylate-containing additive (2800ppm) is added. The mixture is stirred evenly under the action of a vacuum mixer to obtain a positive electrode slurry with a solid content of 65wt%. The positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 12μm, and the aluminum foil is dried at 120℃ for 1h to obtain a positive electrode active material layer with a thickness of 90μm, and the positive electrode active material layer includes 0.01wt% of boron and 0.01wt% of calcium. Repeat the above steps on the other surface of the aluminum foil to obtain a positive electrode sheet coated with a positive electrode active material layer on both sides. Then, after cold pressing, cutting, and welding the pole ears, it was dried under vacuum conditions at 120°C for 1 hour to obtain a positive electrode sheet with a size of 74mm (width) × 854mm (length) and a current collector empty foil area at the tail.

[0116] Alumina (Dv99 is 0.7μm) and binder PVDF are mixed in a mass ratio of 80:20, N-methylpyrrolidone (NMP) is added, and the mixture is stirred evenly under the action of a vacuum mixer to obtain an inorganic coating slurry with a solid content of 30wt%. The inorganic coating slurry is first evenly coated on one surface of the positive current collector aluminum foil at the tail of the above-mentioned positive electrode plate (this surface is defined as the a surface, and the other surface of the current collector is defined as the b surface), and dried at 120°C for 1h to obtain a positive electrode plate with an inorganic coating on one surface of the current collector, i.e., the a surface, the length of the inorganic coating is 95mm, and the thickness of the inorganic coating is 2.5μm.

[0117] Negative electrode: Weigh 100 g of negative electrode active material (artificial graphite with a particle size of 11 μm), 1 g of conductive agent (carbon black), and 4 g of binder (styrene-butadiene rubber, SBR) and add them to 3 g of N-methylpyrrolidone and 120 g of water to form a negative electrode slurry. The negative electrode slurry is stirred, coated, dried, rolled, and spot-welded to the electrode ears to obtain the battery negative electrode.

[0118] Electrolyte: In a glove box filled with argon, first heat EC (ethylene carbonate) at a high temperature of 60°C to convert it into liquid, then prepare a solvent with a mass ratio of EC (ethylene carbonate): DMC (dimethyl carbonate): EMC (ethyl methyl carbonate) = 1:1:1, add 1,3-propanesulfonic acid lactone, 2,2-difluoroethyl acetate, fluorobenzene, 1,2,3-tris(2-cyano)propane and 3-fluoro-4-methylanisole, and then add solid lithium difluorophosphate and prepare it by constant volume method. To a 1.1Mol / L lithium difluorophosphate solution, solid LiFSI accounting for 0.5wt% of the total mass of the electrolyte is added, so that the mass content of 1,3-propanesulfonate accounts for 1wt% of the total mass of the entire electrolyte, the mass content of 2,2-difluoroethyl acetate accounts for 0.5wt% of the total mass of the entire electrolyte, fluorobenzene accounts for 2wt% of the total mass of the electrolyte, 1,2,3-tris(2-cyano)propane accounts for 0.5% of the total mass of the electrolyte, and 3-fluoro-4-methylanisole accounts for 1% of the total mass of the electrolyte.

[0119] Isolation film:

[0120] A 10 μm thick polyethylene (PE) microporous membrane was selected as the base membrane of the isolation membrane, and the difference between the maximum pore size and the minimum pore size of the base membrane was 0.15 μm.

[0121] Organic coating preparation:

[0122] Add the first polymer polypropylene (PP) polymer particles with propylene as the base monomer into the stirrer and stir evenly; add sodium carboxymethyl cellulose into the stirrer and stir evenly; add dimethyl siloxane, a wetting agent, into the stirrer, then add deionized water and stir, adjust the viscosity of the slurry to 45mPa•s and the solid content to 6%, and obtain an organic coating slurry. The organic coating slurry is applied to the inorganic coating on one side of the base film by stripe coating, so that the distance between adjacent bonding points is 120μm, and after drying in an oven, the first coating is obtained. The thickness of the first coating is 3μm. The mass ratio of the first polymer, sodium carboxymethyl cellulose, and dimethyl siloxane is 95:0.5:4.5. Among them, the polymer is spherical or quasi-spherical in the isolation membrane, and the sphericity R of the polymer satisfies 0.7≤R≤1.0.

[0123] Preparation of coating on the other side of the isolation film:

[0124] Inorganic boehmite particles with a Dv50 of 1.3µm and polyacrylate were mixed in a mass ratio of 88:12 and dissolved in deionized water to form an inorganic coating slurry with a solid content of 47%. The resulting inorganic coating slurry was then evenly coated on one side of a PE base film using a micro-concave coating method to obtain a heat-resistant layer, which was then dried in an oven. The thickness of the inorganic coating was 1.8μm.

[0125] The inorganic particle boehmite and the binder polyvinylidene fluoride are mixed at a volume ratio of 1.4, and then N-methylpyrrolidone (a first solvent) is added and uniformly stirred to obtain a coating liquid, wherein the solid content of the coating liquid is 8%; the coating liquid is coated on a porous substrate (polyethylene) by an immersion coating method to form a wet film; the porous substrate (polyethylene) with the wet film is immersed in a coagulation liquid containing deionized water (a third solvent) and N-methylpyrrolidone (NMP, a second solvent) for phase inversion, wherein the mass percentage of N-methylpyrrolidone (a second solvent) in the coagulation liquid is 38%, and the temperatures of the coating liquid and the coagulation liquid are both 25°C; after being immersed in the coagulation liquid for 30 seconds, the coating liquid is placed in an oven and dried at 60°C to obtain an isolation membrane with a porous membrane.

[0126] Preparation of negative electrode sheet: artificial graphite, conductive carbon black, styrene-butadiene rubber (SBR), and carboxymethyl cellulose sodium (CMC) are mixed at a weight ratio of 96.5:1.5:1:1, deionized water is added, and the mixture is stirred evenly under the action of a vacuum mixer to obtain a negative electrode slurry, wherein the solid content of the negative electrode slurry is 75wt%. The negative electrode slurry is evenly coated on one side of the negative electrode current collector copper foil, and dried at 120°C to obtain a negative electrode sheet coated with a negative electrode active material layer with a thickness of 90μm on one side, and the above steps are repeated on the other side of the negative electrode current collector copper foil to obtain a negative electrode sheet coated with a negative electrode active material layer on both sides, and then after cold pressing, cutting, and slitting, a negative electrode sheet with a specification of 476mm×93.5mm is obtained.

[0127] Preparation of lithium-ion batteries: stack the positive electrode sheet, separator, and negative electrode sheet in order, so that the separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role, and wind them to obtain an electrode assembly. After welding the pole ears, place the electrode assembly in an outer packaging aluminum-plastic film, remove moisture at 80°C, inject the above-mentioned electrolyte, and obtain a lithium-ion battery through vacuum packaging, standing, formation, shaping, capacity testing and other processes.

[0128] Examples 1-2 to 1-30, Comparative Examples 1-1 to 1-8

[0129] The preparation of the lithium-ion battery is substantially the same as that of Example 1-1, the only difference being the type and content of the elements in the positive electrode active material layer and the content of lithium difluorophosphate in the electrolyte. The specific parameters are shown in Table 1.

[0130] Example 1-31 to Example 1-33

[0131] The lithium-ion batteries of Examples 1-31 to 1-33 differ from those of Example 1-6 in that the isolation membrane contains a diazine derivative and / or triazine derivative coating, and the specific parameters are shown in Table 1. Taking Example 1-33 as an example, the preparation method of the diazine derivative and triazine derivative coating is as follows: add 15 kg of deionized water solution to a planetary stirring tank, add 2-aminopyrazine material with a Dv50 particle size of 400 nm, mix thoroughly, disperse and stir, then add binder melamine resin and aluminum oxide, so that the weight ratio of 2-aminopyrazine, melamine resin and aluminum oxide is 92:4:4, and stir evenly to form a coating slurry. Then apply the coating slurry to the isolation membrane or to a surface on the existing coating, and the coating thickness is 3 μm.

[0132] The lithium-ion battery was subjected to -10°C voltage drop test, 80°C puncture pass rate test and 60°C intermittent cycle pass rate test. The results are shown in Table 1.

[0133] Table 1

[0134]

[0135] Connect to Table 1

[0136]

[0137] According to Table 1, compared with the comparative example, the -10°C voltage drop of the sodium ion battery in each embodiment is reduced, and the 80°C puncture pass rate and 60°C intermittent cycle pass rate are significantly improved. When the doping element types of the positive electrode active material layer on the positive electrode sheet include at least two or more of boron, calcium, iron and magnesium, and when the content of lithium difluorophosphate in the electrolyte is limited to meet the scope of this application, the lithium ion battery has good low temperature performance and high temperature performance.

[0138] According to Examples 1-1 to 1-16 and Examples 1-22 to 1-28, when the positive electrode active material layer satisfies: 0.01≤B≤0.1; 0.01≤C≤0.1; 0.001≤D≤0.05; 0.05≤E≤0.5, the low temperature performance and high temperature performance of the lithium ion battery are better.

[0139] According to Examples 1-6 and 1-17 to 1-23, when the mass percentage of lithium difluorophosphate in the electrolyte is 0.02% to 0.2%, the lithium-ion battery has good low-temperature performance and high-temperature performance.

[0140] On this basis, according to Examples 1-17 to 1-20, it can be seen that the mass percentage of lithium difluorophosphate in the electrolyte is 0.05% to 0.2%, and the lithium-ion battery has better low-temperature performance and high-temperature performance.

[0141] According to various embodiments and comparative examples, when the lithium-ion battery satisfies 0.2≤(B+C+D+E) / A≤30, the various elements and lithium difluorophosphate have a synergistic effect to improve the low-temperature performance and high-temperature performance of the lithium-ion battery.

[0142] According to Examples 1-6 and 1-31 to 1-33, when the isolation film coating contains diazine derivatives and / or triazine derivatives, the lithium-ion battery has better low-temperature performance and high-temperature performance.

[0143] Example 2-1 to Example 2-47

[0144] The preparation of the lithium-ion battery is substantially the same as that of Example 1-1, except that the contents of lithium difluorophosphate, LiFSI, 1,3-propanesulfonate, 2,2-difluoroethyl acetate, fluorobenzene, 1,2,3-tris(2-cyano)propane and 3-fluoro-4-methylanisole in the electrolyte are different. The specific parameters are shown in Table 2.

[0145] The lithium-ion battery was subjected to a gas production test after being stored at 60°C for 72 hours and an EIS change rate test under fast charging. The results are shown in Table 2.

[0146] Table 2

[0147]

[0148] Continue Table 2

[0149]

[0150] According to Table 2, when the electrolyte includes 1,3-propanesulfonate, 2,2-difluoroethyl lithium bis(fluorosulfonyl)imide acetate, fluorobenzene, 1,2,3-tri(2-cyano)propane and 3-fluoro-4-methylanisole, the lithium ion battery of the present application has a lower gas production after storage at 60°C for 72 hours and a lower EIS change rate under fast charging.

[0151] According to Example 1-1, Example 2-1 to Example 2-12, Example 2-38, and Example 2-39, when F+GF×G in the electrolyte satisfies: 0.5≤F+GF×G≤2.5, the lithium-ion battery has better high temperature performance and fast charging performance.

[0152] On this basis, according to Example 1-1 and Example 2-1 to Example 2-5, it can be seen that when F+GF×G in the electrolyte satisfies: 1≤F+GF×G≤1.9, it has better high temperature performance and fast charging performance.

[0153] According to Examples 2-13 to 2-23, 2-40 and 2-41, when I in the electrolyte satisfies 0.01≤I≤13, the lithium-ion battery has better high temperature performance and fast charging performance.

[0154] On this basis, according to Examples 2-17 to 2-21, when I in the electrolyte satisfies 6≤I≤12, the lithium-ion battery has better high temperature performance and fast charging performance.

[0155] According to Examples 2-24 to 2-29, 2-42 and 2-43, when J in the electrolyte satisfies 1.5≤J≤9, the lithium-ion battery has better high temperature performance and fast charging performance.

[0156] On this basis, according to Examples 2-24 to 2-26, it can be seen that when J in the electrolyte satisfies 1.5≤J≤4.5, the lithium-ion battery has better high temperature performance and fast charging performance.

[0157] According to Examples 2-30 to 2-35, 2-44 and 2-47, when K in the electrolyte satisfies 0.05≤K≤3, the lithium-ion battery has better high temperature performance and fast charging performance.

[0158] On this basis, according to Examples 2-30 to 2-32, it can be seen that when K in the electrolyte satisfies 0.05≤K≤2, the lithium-ion battery has better high temperature performance and fast charging performance.

[0159] According to Example 1-1, Example 2-36 and Example 2-37, when L in the electrolyte satisfies 1≤L≤2.5, the lithium-ion battery has better high temperature performance and fast charging performance.

[0160] According to the embodiment of the present application, when 0.01≤A / G≤0.1 is satisfied in the electrolyte, the lithium-ion battery has better high temperature performance and fast charging performance.

[0161] Example 3-1 to Example 3-21

[0162] The preparation of the lithium-ion battery is roughly the same as that of Example 1-1, with the only differences being the difference H between the maximum pore size and the minimum pore size of the base membrane, the active material particles Dv99, the type of additives in the positive electrode sheet, the functional groups contained in the binder in the positive electrode sheet, and the specific surface area of ​​the conductive agent in the positive electrode sheet. The specific parameters are shown in Table 3.

[0163] The lithium-ion battery was subjected to a gas production test after being stored at 60°C for 72 hours and an EIS change rate test under fast charging. The results are shown in Table 3.

[0164] Table 3

[0165]

[0166] According to Example 1-1, Example 3-1 to Example 3-7, and Example 3-15 to Example 3-16, when Dv99 and H of the positive electrode active material particles in the lithium ion battery satisfy: 600≤Dv99 / H≤4000, the lithium ion battery has better low temperature performance, better mechanical properties and better high temperature performance.

[0167] According to Examples 3-6, 3-8 and 3-17, when the additive in the positive electrode plate is lithium dihydrogen phosphate or aluminum dihydrogen phosphate, the lithium-ion battery has better low-temperature performance, better mechanical properties and better high-temperature performance.

[0168] According to Example 1-1, Example 3-9 and Example 3-18, when the binder in the positive electrode sheet includes a trihydroxybenzene ring or a cyano group, the lithium-ion battery has better low-temperature performance, better mechanical properties and better high-temperature performance.

[0169] According to Examples 3-10 to 3-14, and Examples 3-19 to 3-21, the surface area of ​​the conductive agent in the positive electrode sheet is 650 m 2 / g~900m 2 / g, lithium-ion batteries have better low-temperature performance, better mechanical properties and better high-temperature performance.

[0170] Although the present application has been described with reference to preferred embodiments, various modifications may be made thereto and parts thereof may be replaced with equivalents without departing from the scope of the present application. In particular, the various technical features mentioned in the various embodiments may be combined in any manner as long as there is no structural conflict. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.

Claims

1. An electrochemical device, characterized in that: It includes a positive electrode sheet, an electrolyte, a negative electrode sheet, and a separator disposed between the positive electrode sheet and the negative electrode sheet; The positive electrode plate includes a positive electrode active material layer, the positive electrode active material layer includes two or more of boron, calcium, iron and magnesium, and the boron, calcium, iron or magnesium in the positive electrode active material layer is introduced into the positive electrode active material layer by doping into the positive electrode active material; The electrolyte includes lithium difluorophosphate, and the mass percentage of the lithium difluorophosphate in the electrolyte is A%, and the value range of A satisfies: 0.02≤A≤0.5; The electrolyte further comprises lithium bis(fluorosulfonyl)imide, wherein the mass percentage of the lithium bis(fluorosulfonyl)imide in the electrolyte is G%, and the value range of A / G satisfies: 0.01≤A / G≤0.1; The positive electrode active material layer satisfies at least one of the following conditions: (1) The mass percentage content of the boron element in the positive electrode active material layer is B%, and the value range of B satisfies: 0.01≤B≤0.1; (2) The mass percentage content of the calcium element in the positive electrode active material layer is C%, and the value range of C satisfies: 0.01≤C≤0.1; (3) The mass percentage content of the iron element in the positive electrode active material layer is D%, and the value range of D satisfies: 0.001≤D≤0.05; (4) The mass percentage content of the magnesium element in the positive electrode active material layer is E%, and the value range of E satisfies: 0.05≤E≤0.

5.

2. The electrochemical device according to claim 1, characterized in that The mass percentage of the lithium difluorophosphate in the electrolyte is A%, and the value range of A satisfies: 0.02≤A≤0.

2.

3. The electrochemical device according to claim 1, characterized in that The mass percentage of the lithium difluorophosphate in the electrolyte is A%, and the value range of A satisfies: 0.05≤A≤0.

2.

4. The electrochemical device according to claim 1, characterized in that: The mass percentage of the boron element in the positive electrode active material layer is B%, the mass percentage of the calcium element in the positive electrode active material layer is C%, the mass percentage of the iron element in the positive electrode active material layer is D%, and the mass percentage of the magnesium element in the positive electrode active material layer is E%, and (B+C+D+E) / A satisfies: 0.2≤(B+C+D+E) / A≤30.

5. The electrochemical device according to claim 1, characterized in that The electrolyte also includes 1,3-propane sultone. The mass percentage of the 1,3-propane sultone in the electrolyte is F%, and the value range of F+GF×G satisfies: 0.5≤F+GF×G≤2.

5.

6. The electrochemical device according to claim 1, characterized in that The electrolyte also includes 1,3-propane sultone, and the mass percentage of the 1,3-propane sultone in the electrolyte is F%, and the value range of F+GF×G satisfies: 1≤F+GF×G≤1.

9.

7. The electrochemical device according to claim 1, characterized in that The isolation membrane includes a base membrane, and the difference between the maximum pore size and the minimum pore size of the base membrane is H; The positive electrode active material layer further includes positive electrode active material particles, and Dv99 and H of the positive electrode active material particles satisfy: 600≤Dv99 / H≤4000.

8. The electrochemical device according to claim 1, characterized in that The isolation film includes a coating layer, and the coating layer includes one or more of a diazine derivative and a triazine derivative.

9. The electrochemical device according to claim 1, characterized in that The positive electrode plate further includes an additive, wherein the additive includes one or more of lithium dihydrogen phosphate and aluminum dihydrogen phosphate; And / or, the positive electrode plate further comprises a binder, wherein the binder comprises at least one functional group selected from the group consisting of a trihydroxybenzene ring and a cyano group; And / or, the positive electrode plate further comprises a conductive agent, the specific surface area of ​​the conductive agent is 650m 2 / g~900m 2 / g.

10. The electrochemical device according to claim 1, characterized in that The electrolyte satisfies at least one of the following conditions: (1) The electrolyte further comprises 2,2-difluoroethyl acetate, wherein the mass percentage of the 2,2-difluoroethyl acetate in the electrolyte is 1%, and the value range of I satisfies: 0.01≤I≤13; (2) The electrolyte further comprises fluorobenzene, and the mass percentage of the fluorobenzene in the electrolyte is J%, and the value range of J satisfies: 1.5≤J≤9; (3) The electrolyte further comprises 1,2,3-tris(2-cyano)propane, and the mass percentage content of the 1,2,3-tris(2-cyano)propane in the electrolyte is K%, and the value range of K satisfies: 0.05≤K≤3; (4) The electrolyte further comprises 3-fluoro-4-methylanisole, and the mass percentage of 3-fluoro-4-methylanisole in the electrolyte is L%, and the value range of L satisfies: 1≤L≤2.

5.

11. The electrochemical device according to claim 10, characterized in that The electrolyte satisfies at least one of the following conditions: (1) The value range of I satisfies: 6≤I≤12; (2) The value range of J satisfies: 1.5≤J≤4.5; (3) The value range of K satisfies: 0.05≤K≤2.

12. An electronic device, characterized in that: An electrochemical device comprising any one of claims 1-11.

Citation Information

Patent Citations

  • Composite battery

    CN102651491A

  • Electrochemical device and electronic device

    CN115398700A